Micropropagation of Paphiopedilum x Dalatense - Vinh, Tran Thai; Bing, H’ Yon Niê; Tham, Dang Thi; Hang, Nguyen Thi Thanh; Cong, Vu Kim; Duy, Nong Van (Vietnam Journal of Biotechnology, 2021)
Paphiopedilum x dalatense is a beautiful orchid species with large flowers in variable colors and leaves covered with stripes and beautiful unseen mosaic spots. Recently, many people exploit this species, causing it becomes very rare. In this study, we studied the effects of various organic matter: potato, banana and tryptone, yeast powder, peptone on the growth and development of P. dalatense shoots as well as the effects of NAA and humic acid on in vitro rooting of this orchid were investigated. The research results showed that MS medium supplemented with 100 g/L banana in combination with 100 g/L potato (5,4 shoots/sample, 18,8 mm/shoot, 4,5 leaves/shoot, and shoots survival rate of 100%) or MS medium supplemented with 1 g/L peptone (4,19 shoots/sample, 15 mm/shoot, 4 leaves/bud, and 92% of shoots survival rate) were the best response for the shoot formation and development. In addition, the half strength MS culture medium supplemented with 1 mg/L NAA (5,2 leaves/sample, 4,6 roots/buds, 3,56 cm/root, and 100% rate for rooting) was the suitable medium for the in vitro rooting of P. dalatense. Being cultured on half strength MS medium supplemented with 2 mg/L humic acid, the rooting rate reached 100% with the greatest root number and the longest root (5 roots/shoots, 5,5 cm/root). The obtained results on the in vitro propagation on this orchid helps contribute to the conservation and increases the genotic pool of this precious wild orchid species, as well as the rapid multiplication of healthy plantlets serving the commercialization of precious orchid species.